Passive temperature sensing through chipless vanadium dioxide metasurface tags - Fuwei Wang; Rong Sun; Xuechen Zhang; Yanzheng Liu; Mei Qi; Chen He (Scientific Reports)
Abstract Passive temperature sensing systems based on the Internet of Things (IoT) present an efficient, reliable, and convenient solution for temperature monitoring with extensive application prospects and market value. This paper introduces a passive, battery-free, chipless, metasurface temperature sensing tag. The key insight is that the sensing tag uses vanadium dioxide ( $$\hbox{VO}_{2}$$ ) to solve the problems of measuring distance, large size, and high cost related to active devices. The sensing tag fabricated with tungsten-doped $$\hbox{VO}_{2}$$ powder demonstrated a significant variation in the reflection magnitude within the temperature range of 34–42 °C. It was achieved through coating, sintering, metasurface design, and ion beam etching. Experimental results showed that the square resistance of the prepared coating decreased from 1003 to 90 $${Ω }/{\square }$$ as the temperature increased from 34 to 42 °C. Additionally, the reflection magnitude of the tag significantly increased with the temperature decrease in the 3.5–5.27 GHz frequency band. These results indicate that the passive temperature sensing tags can achieve rapid and accurate temperature sensing within the 34–42 °C range.